Synthesis of Hydroxamic Ligands with Transition Metal Complexes, their Biological Activities and Characterization Through Spectroscopic Techniques - Saleem, Farzana; Khan, Naqeebullah; Samiullah; Attiq-ur-Rehman; Ali, Irshad (Al-Nahrain Journal of Science, 2020)
New metal complexes including Ni (Ⅱ), Co (Ⅱ), Cu (Ⅱ), Fe (Ⅲ), Cr (Ⅲ), Cd (Ⅱ) and Zn (Ⅱ) have been synthesized from parent ligand N-methyl m-nitrobenzohydroxamic acid. The condensation ratio is 2:1 of the ligand and metal salt (MX) in methanol. The ligand N-methyl m-nitrobenzohydroxamic has been prepared by the interaction of N-methylhydroxylamine hydrochloride with m-nitrobenzoyl chloride. The coordination modes and bonding of the ligands along with its metal complexes have been identified by FT-IR, 1H-NMR and UV-Vis spectroscopic techniques. It has been enumerated by spectroscopic techniques that the complex is formed via O, O-coordination to metal through the oxygen of carbonyl group and deprotonated hydroxyl group. The antibacterial and antifungal activities of the ligand as well as its complexes have been estimated against two gram negative strains such as Escherichia coli and Salmonella typhi, one gram positive strain Escherichia coli and one fungal strain yeast. In addition to this the cytotoxicity and antitumor activities have been evaluated resistant to Brine shrimps eggs and Hela cell line respectively.